PENGARUH HERDING, OVERCONFIDENCE, RISK PERCEPTION, DAN ACCOUNTING KNOWLEDGE TERHADAP KEPUTUSAN INVESTASI DI BURSA SAHAM: Studi Pada Pelaku Investasi Bursa Saham di DIY - Kuasa, Norma Norahayu; Tjahjono, Achmad (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The effect of herding, overconfidence, accounting knowledge and risk perception on investment decisions on the stock market. In today unstable economic conditions, investment is one of the decisions to save or even seek additional income. Investors are competing to benefit from every investment decision they make. Based on this, this study aims to analyze what factors influence investment decisions. This study will examine the effect of herding, overconfidence, risk perception, and accounting knowledge variables on investment decisions. The respondents of this research are investors in Yogyakarta who invest in the stock market. The number of samples in this study were 101 respondents with simple random sampling technique. The analysis of this research uses the help of the IBM SPSS program. The results of this study indicate that accounting knowledge has a positive and significant influence on investment decisions. However, herding, overconfidence, and risk perception do not have a positive and significant influence on investment decisions. Although there are variables that partially have no effect on investment decisions, this study finds that simultaneously all variables have an influence on investment decisions. The limitations of this study include the number of variables that are still small when compared to the existing population. In addition, researchers also did not select investors based on the category or type of investment made. In addition, this study found that the dependent variables in this study only had an effect of 27,8 percent to the independent variable (Investment Decision). Based on the result there are many more factors that influence investment decision.